THE LAW PROTECTION ON STATE CIVIL APPARATUS WITH STATUS OF GOVERNMENT EMPLOYEES WITH EMPLOYMENT AGREEMENT BASED ON STATE CIVIL APPARATUS LAW - Robert Julian Saragih; Amancik Amancik; Iskandar Iskandar (Universitas Bengkulu, 2022)
The issuance of Law Number 5 of 2014 concerning state civil apparatus (Further will be referred as ASN) provides a new paradigm in the world of employment in Indonesia with the presence of the term Government Employee with a Work Agreement (Further will be referred as PPPK). However, the legal relationship of PPPK is unique because there is a point of contact between public law and private law so that legal protection for PPPK is still very weak. This study discussed how the law position of the PPPK and the law effort that can be taken by the PPPK in the event of a Termination of Employment Contracts (Further will be referred as PHPK). The research method used was normative juridical law research by using a statutory approach and analyzing various statutory regulations that cover it. The results of this study indicated that the law position of PPPK as ASN is felt to be very weak and in the case of PHPK normatively, it also does not provide law certainty for PPPK. In this case, the government and the House of Representatives (Further will be referred as DPR) should make changes or revoke the ASN Law to abolish the regulatory provisions regarding PPPK and also to provide clarity regarding the provisions of the civil service court in the event of PHPK for PPPK. In this case the ASN Law must also be followed by fundamental changes in the provisions of the State Administrative Court and the on Government Administration Law.